Power coupling mode transitions induced by tailored voltage waveforms in capacitive oxygen discharges. (7th February 2017) - Derzsi, Aranka; Bruneau, Bastien; Gibson, Andrew Robert; Johnson, Erik; O'Connell, Deborah; Gans, Timo; Booth, Jean-Paul; Donkó, Zoltán
Abstract: Low-pressure capacitively coupled radio frequency discharges operated in O2 and driven by tailored voltage waveforms are investigated experimentally and by means of kinetic simulations. Pulse-type (peaks/valleys) and sawtooth-type voltage waveforms that consist of up to four consecutive harmonics of the fundamental frequency are used to study the amplitude asymmetry effect as well as the slope asymmetry effect at different fundamental frequencies (5, 10, and 15 MHz) and at different pressures (50–700 mTorr). Values of the DC self-bias determined experimentally and spatio-temporal excitation rates derived from phase resolved optical emission spectroscopy measurements are compared with particle-in-cell/Monte Carlo collisions simulations. The spatio-temporal distributions of the excitation rate obtained from experiments are well reproduced by the simulations. Transitions of the discharge electron heating mode from the drift-ambipolar mode to the α -mode are induced by changing the number of consecutive harmonics included in the driving voltage waveform or by changing the gas pressure. Changing the number of harmonics in the waveform has a strong effect on the electronegativity of the discharge, on the generation of the DC self-bias and on the control of ion properties at the electrodes, both for pulse-type, as well as sawtooth-type driving voltage waveforms The effect of the surface quenching rate of oxygen singlet delta metastable molecules on the spatio-temporal excitation patterns is also investigated.